The Diatoms in Four Postglacial Deposits in Greenland. - Foged, Niels (Meddelelser om Grønland, 1972)
Diatoms have been determined and counted in 4 series of samples through postglacial deposits in Greenland covering from 2 to more than 9 millennia. Interpretations of the ecological conditions and changes in the investigated lakes and bogs are presented. 3 new taxa: Neidium iridis (EHR.) CLEVE fo. elliptica nov. fo., Neidium iridis (EHR.) CLEVE var. porsildii nov. var. and Eunotia faba (EHR.) GRUN. var. rhomboidea nov. var., besides one transfer: Pinnularia Piridis (NnzscH} EHR. fo. cuneata (E. ØSTRUP, A. CLEVE} nov. comb. are described.